Kahaniyon Ka Jungle - Qayyum, nazar (Ferozsons (PVT) LTD Lahore, 2010)
Kahaniyon Ka Jungle is a captivating collection of stories that take readers on an imaginative journey through a jungle filled with magical creatures and exciting adventures.